Hubungan Status Imunisasi dengan Kejadian Diare pada Balita Usia 3-5 Tahun di Kelurahan Baloi Permai Wilayah Kerja Puskesmas Baloi Permai Kota Batam Tahun 2023 - Pitria Ramadani; Nelli Roza; T. Eltrikanawati (Universitas Muhammadiyah Manado, 2024)
This study aims to identify and determine the relationship between immunization status and the incidence of diarrhea in toddlers aged 3-5 years. The sample in this study amounted to 72 toddlers, namely 36 cases (diarrhea) and 36 controls (no diarrhea). This study uses Case Control design with systematic sampling technique and Chi Square data analysis. The results showed a relationship between immunization status and the incidence of diarrhea in toddlers with a significance value of 0,03 < α (0,05). Children with incomplete immunization are more at risk of suffering from diarrhea with Odd Ratio = 2.864. To prevent the occurrence of diarrhea in toddlers, health centers can provide information or provide counseling and education about the importance of immunization and improve efforts to overcome risk factors for diarrhea in toddlers.